The Implementation Of Scientific Approach Based On English Learning Strategy (SABELS) To The Students’ Ability In Reading Comprehension - Rizky Khairunnisa Sormin; Ika Purnama Sari; Anita Purba (Universitas Riau, 2023)
This research aims to apply The Scientific Approach-Based English Learning Strategy (SABELS) on the students’ ability in comprehending text fourth semester students of STIKOM Tunas Bangsa. This research is descriptive qualitative, because the researcher used descriptive method to analize the data and the data are in the form of word. This research conducted in STIKOM Tunas Bangsa Pematangsiantar. The researcher used three techniques to collecting the data. Those are observation, interview and study document. The researcher did two observations in class. The subject of the interview is the teacher as implementer the teaching learning process. The research findings are (1) the Implementation of the Scientific Approach in the Teaching of Reading Comprehension to the fourth semester students at STIKOM Tunas Bangsa was good, because was appropriate with the regulation, (2) in applying scientific approach, the teacher used five phase, those are observing, questioning, experimenting, associating, and communicating. The teacher used authentic assessment in the evaluation. Based on the second meeting, the English teacher uses writing test to assess the cognitive aspect of the students. Finally, by knowing the result, it is better if English teachers apply the SABELS to improve the students’ achievement.